List Stefana Napierskiego do Wandy i Seweryna Pollaków - Wasąg, Magdalena (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2014)
A letter from Stefan Napierski to his secretary and friend in charge of the artist's library, and his wife.